Metrics for assessing physician activity using electronic health record log data. (6th February 2020) - Sinsky, Christine A; Rule, Adam; Cohen, Genna; Arndt, Brian G; Shanafelt, Tait D; Sharp, Christopher D; Baxter, Sally L; Tai-Seale, Ming; Yan, Sherry; Chen, You; Adler-Milstein, Julia; Hribar, Michelle
Abstract: Electronic health record (EHR) log data have shown promise in measuring physician time spent on clinical activities, contributing to deeper understanding and further optimization of the clinical environment. In this article, we propose 7 core measures of EHR use that reflect multiple dimensions of practice efficiency: total EHR time, work outside of work, time on documentation, time on prescriptions, inbox time, teamwork for orders, and an aspirational measure for the amount of undivided attention patients receive from their physicians during an encounter, undivided attention. We also illustrate sample use cases for these measures for multiple stakeholders. Finally, standardization of EHR log data measure specifications, as outlined here, will foster cross-study synthesis and comparative research.